2013
DOI: 10.7763/ijcea.2013.v4.331
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of Esterification of Palmitic acid with Ethanol- Optimization Using Statistical Design of Experiments

Abstract: Abstract-The aim of this study was to apply statistical design of experiments for optimization of esterification reaction and to obtain the kinetics of the reaction. The present system of study was palmitic acid with ethanol using homogeneous catalyst sulphuric acid. The reactions were performed in a batch reactor and the progress of the reaction was monitored using Karl Fischer Titrator. To reduce the number of experiments and in order to achieve optimum conditions of the reaction, statistical design of exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 14 publications
1
13
0
Order By: Relevance
“…Apparent activation energies for palmitic acid esterication over the 210 and 430 nm macropore hierarchical catalysts also indicate a switchover from diffusion limited to reaction-rate limited esterication with increasing macropore size, rising from 34 AE 3 kJ mol À1 (210 nm) to 45 AE 3 kJ mol À1 (430 nm). The latter barrier is in fair agreement with the homogeneous acid catalysed value of 56 kJ mol À1 , 42 suggesting that esterication over the 430 nm macropore catalyst is largely free from mass transport limitations.…”
Section: Catalytic Enhancement Through Macropore Tuningsupporting
confidence: 70%
See 1 more Smart Citation
“…Apparent activation energies for palmitic acid esterication over the 210 and 430 nm macropore hierarchical catalysts also indicate a switchover from diffusion limited to reaction-rate limited esterication with increasing macropore size, rising from 34 AE 3 kJ mol À1 (210 nm) to 45 AE 3 kJ mol À1 (430 nm). The latter barrier is in fair agreement with the homogeneous acid catalysed value of 56 kJ mol À1 , 42 suggesting that esterication over the 430 nm macropore catalyst is largely free from mass transport limitations.…”
Section: Catalytic Enhancement Through Macropore Tuningsupporting
confidence: 70%
“…For propanoic acid, esterication was independent of macropore size, as may be anticipated from its small kinetic diameter ($0.48 nm) and hence minimal diffusive restriction by the pore network. A recent PFG NMR study on organic acid diffusion through mesoporous SBA-15 and KIT-6 silicas 47 reported that the effective tortuosity increased with acid chain length, and that pore walls enhanced diffusion possibly by disrupting the dynamic hydrogen bonding network present throughout the liquid mixture (as has previously observed for polyols and polyol/ methanol mixtures [41][42][43][44] ). It follows that propanoic acid selfdiffusion may be dominated by hydrogen-bonding dynamics, rather than by pore network tortuosity, consistent with the present ndings that propanoic acid TOF and D 0 /D iso (equated here to macropore size) are uncorrelated.…”
Section: Structure-reactivity Correlationsmentioning
confidence: 68%
“…4 b and 5 b show the influence of both the catalyst concentration (P 2 ) and A/V 0 (P 4 ) on the conversion and water flux. With an increase in the amount of catalyst, the conversion of acrylic acid rises due to the availability of more H + ions which enhances the reaction producing more conversion [31,32]. The plot in Fig.…”
Section: Effects Of Variables On Conversion Of Acrylic Acid and Watermentioning
confidence: 99%
“…4 a-f and 5 a-f, respectively. According to Beula and Sai [31], closer contour lines require the less amount of variables and a wide gap between contour lines indicates the demand of a high quantity of variables for enhancement in response. Figs.…”
Section: Effects Of Variables On Conversion Of Acrylic Acid and Watermentioning
confidence: 99%
See 1 more Smart Citation